Characteristics of Buddhist Politicians for Public Interest Devotion in Thai Society - Nipakasem, Mathayom; Mahatthanadull, Sanu; Phramaha Nantakorn Piyabhani (The Journal of International Buddhist Studies College, 2024)
This article aimed to (1) explore the issues facing Thai politicians and the concept of public interest, (2) explore Buddhist teachings relevant to politicians, (3) present the characteristics of Buddhist politicians for public interest devotion in Thai society. The data collection tool utilized for this research involved conducting in-depth interviews with ten key informants, including four senior monks, one former Prime Minister, and four scholars. The analysis of the gathered data was conducted through the method of content analysis. The findings of the study revealed the following: The challenges confronting Thai politicians encompass various ethical dilemmas present in their behaviors, communication, and mindset. These challenges revolve around issues such as conflicts of interest and instances of corruption. Furthermore, the exploration of public interest entails an examination of the realm of politics, the conduct of politicians, and their ethical obligations, all of which have the potential to give rise to conflicts of interest and corrupt practices. The Buddhist teachings that hold relevance for politicians encompass a wide array of guidance for the functioning of political systems. These teachings include concepts such as (1) lddhipāda (Path of Accomplishment), (2) Brahmavihāra (Sublime States of Mind), (3) Kusala-kammapatha (Wholesome Course of Actions), (4) Dassa-rājadhamma (Virtues of the Rulers), (5) Cakkavatti-vatta (Duties of a Great Ruler), (6) Rāja-sangaha-vatthu (Bases of Sympathy), (7) Agati (Wrong Courses of Behavior), (8) Sappurisa-dhamma Qualities of a Genuine Person, (9) Aparihāniya-dhamma (Things Leading Never to Decline but Only to Prosperity),and (10) Attha (Benefit or Welfare). The characteristics defining Buddhist politicians who are dedicated to public interest within Thai society encompass ethical and moral aspects, behavioral traits, mental attributes, and a perspective centered on public welfare. These characteristics include qualities such as being a just ruler, possessing trustworthiness, engaging in righteous conduct in both speech and actions, demonstrating active participation, upholding a commitment to justice, embracing a sense of responsibility, displaying passion and dedication, adhering to a particular ideology, exercising sound judgment, nurturing a mindset that prioritizes non-greed, embodying a spirit of devotion (social altruism), and exemplifying traits of loving-kindness. These four characteristics collectively embody the concept of "Bhāvitā," which comprises physical development (Bhāvikāya), moral development (Bhāvisīla), emotional or mental development (Bhāvicitta), and wisdom development (Bhāvipaññā). In conclusion, the adoption of Buddhist principles by politicians is crucial for fostering a political environment characterized by integrity, accountability, and ethical behavior. This alignment not only addresses the immediate ethical challenges within governance but also promotes sustainable societal progress. Through these principles, politicians can effectively contribute to the creation of a just and harmonious society, benefiting all citizens and enhancing the overall quality of governance in Thailand.